STRESS DAN CARA MENGURANGINYA - Sukadiyanto Sukadiyanto (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Stressand How to Reduce It. Everyone experiences stress or tension but it will vary from person to person. The difference lies in its intensity and the way to respond to its causes. Some ways to reduce stress include, among others, consuming healthy and nutritious foods, maintaining physical fitness, doing breath exercises, doing relaxation exercises, doing fun activities, taking a vacation, establishing harmonious relationship, avoiding bad habits, planning daily routines, keeping plants and animals, sparing time for oneself or families, and avoiding loneliness. A stress-reducing program can be successful if it is seriously carried out with discipline.Keywords: stress, a stress-reducing program